2020
DOI: 10.1128/mbio.00804-20
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Chromatin Proteins Cren7 and Sul7d Compact DNA by Bending and Bridging

Abstract: Archaeal chromatin proteins Cren7 and Sul7d from Sulfolobus are DNA benders. To better understand their architectural roles in chromosomal DNA organization, we analyzed DNA compaction by Cren7 and Sis7d, a Sul7d family member, from Sulfolobus islandicus at the single-molecule (SM) level by total single-molecule internal reflection fluorescence microscopy (SM-TIRFM) and atomic force microscopy (AFM). We show that both Cren7 and Sis7d were able to compact singly tethered λ DNA into a highly condensed structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
(74 reference statements)
2
20
0
Order By: Relevance
“…This hypothesis has recently been revisited as Alba was shown to be a general nucleic acid-binding protein interacting with RNA as well (Guo et al 2014). Besides Alba, the NAP Cren7 is highly conserved in not only the Sulfolobales but also all Crenarchaeota; Cren7 is a versatile architectural protein, bending and also bridging DNA, thereby forming highly condensed chromatin filaments (Guo et al 2008;Zhang et al 2019cZhang et al , 2020. Sul7d, analogous to Cren7, is a monomeric protein, which is capable of bending DNA; it has been found in many Sulfolobales genera: Sulfolobus and Saccharolobus, Acidianus, Metallosphaera, Stygiolobus and Sul- furisphaera (Kalichuk et al 2016).…”
Section: Chromosome Packaging and Structuringmentioning
confidence: 99%
“…This hypothesis has recently been revisited as Alba was shown to be a general nucleic acid-binding protein interacting with RNA as well (Guo et al 2014). Besides Alba, the NAP Cren7 is highly conserved in not only the Sulfolobales but also all Crenarchaeota; Cren7 is a versatile architectural protein, bending and also bridging DNA, thereby forming highly condensed chromatin filaments (Guo et al 2008;Zhang et al 2019cZhang et al , 2020. Sul7d, analogous to Cren7, is a monomeric protein, which is capable of bending DNA; it has been found in many Sulfolobales genera: Sulfolobus and Saccharolobus, Acidianus, Metallosphaera, Stygiolobus and Sul- furisphaera (Kalichuk et al 2016).…”
Section: Chromosome Packaging and Structuringmentioning
confidence: 99%
“…Mass spectrometry analysis has also revealed the presence of the major host chromatin protein of the Sul7d family in the highly purified SSV1 virions, suggesting its involvement in condensation of the viral DNA (Quemin et al, 2015). In vitro studies have demonstrated that Sul7d proteins bind dsDNA nonspecifically and induce negative supercoiling and compaction of relaxed and positively supercoiled DNA (López-García et al, 1998;Zhang et al, 2020b). Notably, the DNA isolated from SSV1 virions was found to be positively supercoiled by reverse gyrase (Nadal et al, 1986) and can thus be efficiently condensed by the Sul7d proteins.…”
Section: Fuselloviridae Familymentioning
confidence: 99%
“…To further explore the behavior of Cren7 WT on DNA, we cross-linked the protein in the presence of nicked pBR322 DNA with 0.2% glutaraldehyde and visualized the Cren7 WT -DNA complexes by AFM. As shown in Figure 2D, the crosslinked Cren7 WT -DNA complexes superficially resemble those of the rCren7-DNA complexes (Zhang et al, 2020). At the protein/DNA ratio (in monomer/bp) of 1:10, a physiologically relevant ratio, highly condensed core-like structures, which appeared to form along the DNA strand, presumably, as a result of lateral interaction between adjacently bound Cren7 monomers (Figure 2D).…”
Section: Protein Methylation Prevents Dna Bridging and Not Dna Packag...mentioning
confidence: 86%
“…It binds double-stranded DNA in the minor groove, inducing a severe DNA bending toward the major groove ( Zhang et al, 2010 ), and thus folds DNA into an S-shape chromatin fiber ( Zhang et al, 2019 ). The protein protects DNA duplex from thermal denaturation, constrains negative DNA supercoils and compacts DNA efficiently via bending and bridging in vitro ( Guo et al, 2008 ; Zhang et al, 2020 ). Of the 12 lysines of Cren7 from S. islandicus , 9 were found to be methylated, among which K16 underwent both mono- and dimethylation ( Cao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%